Desafíos de la sociedad de la información: calidad de la investigación universitaria - La Rosa Pineda, Amaro (2010)
Theauthorstarts fromthecomprehension of scientific research as fundamental activity of the university, examining basic research criteria based on evidence and quality demands for university research as well as for the evaluation of lnternetpublished information.